Aging affects motor planning for grasping everyday objects: A case control study - Guillaume Galliou; Lucette Toussaint; Thomas Rulleau (PLoS ONE, 2026)
Background and purpose The ability to anticipate the movement of objects to be grasped is essential for older people to remain independent in their daily lives and to avoid accidents at home. This study was designed to investigate how normal aging affects motor planning for the grasping of everyday objects. Method Sixty-nine right-handed adults with no cognitive impairment participated in the study. They were divided according to age into a young group (n = 30, aged 18–30 years) or an old group (n = 39, aged 65 years and older). Their motor-planning abilities were assessed using an object-grasping judgment task, their manual dexterity with a timed peg placement task and their motor imagery abilities with the Vividness of Movement Imagery Questionnaire. For all variables, a nonparametric Mann–Whitney U test was used to identify differences between the two groups. Spearman’s rho correlation was used to examine the relationships between motor-planning ability and manual dexterity score, as well as between motor-planning ability and motor imagery ability, in each group. Results and discussion Compared with the young group, the old group took longer to choose the correct grasp during the object-grasping judgment task and had poorer manual dexterity. Analysis of the correlations suggested that the older participants who had the longest response times in the object-grasping judgment task tended to place the fewest pegs in the manual dexterity task and to have the lowest motor imagery skills. Conclusions Aging may affect motor planning in a particular way. It does not affect the ability to build the expected motor plan, but appears to slow down the information processing needed to build that plan. This difficulty seems to be linked to the decline in manual dexterity and motor imagery skills as people age.